New mutations of acetylcholinesterase in Bactrocera dorsalis populations across southern China and impact on resistance to organophosphate - Yinjun Fan; Xinyi Dong; Dan Yang; Yu Qin; Xueping Hu; Hongxu Zhou (Ecotoxicology and Environmental Safety)
Bactrocera dorsalis, a highly destructive and invasive fruit pest, has spread from the south to the north, significantly increasing the risk to agricultural and horticultural crops worldwide. Currently, chemical insecticides remain the primary method of controlling B. dorsalis. Chlorpyrifos, an organophosphate insecticide, has become the main alternative in China following the 2008 ban on five highly toxic organophosphates. However, the current status of resistance and its underlying mechanisms remain largely unclear. The study monitored the resistance levels of five field populations in China, revealing moderate resistance to chlorpyrifos (resistance ratios 7.57–17.06-fold). Six mutations (I214V, G420A, G488S, Q643R, H645L and T659A) in the target acetylcholinesterase 2 (AChE2) of chlorpyrifos were firstly identified, with high heterogeneity among field populations. This significant association were found between the G420A mutation frequency and chlorpyrifos resistance, evidence in both the individual survival rates and the population resistance levels. In vitro expression of ten AChE2 variation showed G420A conferred greater reduced sensitivity to chlopyrifos than other mutations, while H645L and T659A combined with Q643R increased sensitivity. Most variants retained substantial substrate hydrolysis activity. We compared twelve mutations in AChE2 reported in insects and discussed their implications. These provides critical insights into B. dorsalis control strategies and the development of more effective insecticides targeting AChE2 in insects.